A guide to best practices for the transition from ipv4 to ipv6 (2015)
This article presents a proposal for a guide to best practices to support Information Technology [IT] areas in the planning and implementation of the transition of their infrastructure and technology services to IPv6 protocol. For this purpose an analysis of references was done to identify the problem, comprehend the state of the art; the current state of advance in the migration to IPv6 and its implementation worldwide; the state of the art of technology in the regions where it is a key factor and the process that these regions have developed to explore and implement the transition from IPv4 to IPv6, and as an analysis of the manner in which their governments assumed this transition; the identification of how the processes of the model of best practices for IT, ITIL v.3 can support the transition; and the existing mechanisms of technological transition from IPv4 to IPv6 according to two scenarios: with and without IPv4 and IPv6 coexisting.